Descriptions of three new neotropical species of Acleris Hiibner, 1825 (Lepidoptera Tortricidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Three new species, viz., Acleris magnisignis, A. mutila from Mexicoand A. brusqueana from Brazil are described. Pive species known till now fromthe Neotropics are discussed.
Keywords: Acleris; Lepidoptera; Tortricidae; Tortricini; Neotropical; new species